Membrane-bound Atp-dependent Energy Systems and the Gastrointestinal Mucosal Damage and Protection - Mozsik, Gyula; Szabo, Imre (IntechOpen, 2016)
The book on Membrane-bound Atp-dependent Energy Systems and the Gastrointestinal Mucosal Damage and Protection deals with various aspects of peptic ulcer disease, like clinical pharmacology, nutrition, molecular biochemical pharmacology as well as clinical aspects, and especially with the evaluation of certain biochemical mechanisms in human gastric mucosa and in animal gastric tissues obtained from different ulcer models. This book can be useful to physiologists; biochemists; pharmacologists, particularly molecular and biochemical pharmacologists; internists; gastroenterologists; biologists; surgeons and pharmacists.